2015
DOI: 10.1371/journal.pone.0137824
|View full text |Cite
|
Sign up to set email alerts
|

Patient Empowerment Improved Perioperative Quality of Care in Cancer Patients Aged ≥ 65 Years – A Randomized Controlled Trial

Abstract: PurposeThis randomized controlled, clinical prospective interventional trial was aimed at exploring the effect of patient empowerment on short- and long-term outcomes after major oncologic surgery in elderly cancer patients.MethodsThis trial was performed from February 2011 to January 2014 at two tertiary medical centers in Germany. The study included patients aged 65 years and older undergoing elective surgery for gastro-intestinal, genitourinary, and thoracic cancer. The patients were randomly assigned to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 69 publications
0
45
0
11
Order By: Relevance
“…Most individual RCTs analysed fewer than 60% of the sample originally recruited in the study, excluding participants due to comorbidity or inability to undergo cardiopulmonary exercise testing. Participants were adults with colorectal (Carli et al, ; Cheville et al, ; Gillis et al, ; Moriya, ) lung (Barlési et al, ; Stefanelli et al, ), head and neck (Van Bokhorst‐de Van der Schuer et al, ), breast (Garssen et al, ), bladder (Jensen, Krintel Petersen, Jensen, Lausten, & Borre, ; Jensen, Petersen, Jensen, Laustsen, & Borre, ) and prostate (Bales et al, ; Burgio et al, ; Parker et al, ) cancer or included individuals with a range of cancers (Schmidt et al, ). Trial designs were primarily feasibility studies, and therefore, the studies were rarely powered to determine the efficacy of prehabilitation on post‐treatment recovery outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most individual RCTs analysed fewer than 60% of the sample originally recruited in the study, excluding participants due to comorbidity or inability to undergo cardiopulmonary exercise testing. Participants were adults with colorectal (Carli et al, ; Cheville et al, ; Gillis et al, ; Moriya, ) lung (Barlési et al, ; Stefanelli et al, ), head and neck (Van Bokhorst‐de Van der Schuer et al, ), breast (Garssen et al, ), bladder (Jensen, Krintel Petersen, Jensen, Lausten, & Borre, ; Jensen, Petersen, Jensen, Laustsen, & Borre, ) and prostate (Bales et al, ; Burgio et al, ; Parker et al, ) cancer or included individuals with a range of cancers (Schmidt et al, ). Trial designs were primarily feasibility studies, and therefore, the studies were rarely powered to determine the efficacy of prehabilitation on post‐treatment recovery outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The primary endpoint was predominantly objective physical function prior to treatment with the secondary endpoints described at 1–6 months post‐intervention. Only four (25%) of the authors fully reported participant comorbidities at baseline (Burgio et al, ; Jensen et al, ; Schmidt et al, ; Van Bokhorst‐de Van der Schuer et al, ) while two actively excluded participants with comorbidities possibly due to the intensity of the exercise programme (Carli et al, ; Stefanelli et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Already existing psycho-pedagogical tools to increase knowledge about the disease show that specific and clear disease information increases patient empowerment and participation. From participation grows knowledge (Alden, 2014; Kane, 2014; Schmidt et al, 2015). There are several studies as well as patient testimonies pointing to the importance of patient participation and self-action in both diagnostic and treatment processes (deBronkart, 2011; McDonald, Bryce, & Graber, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, such as ERAS [1] and PER-ATECS [2], have already shown that the field of anesthesiology plays a significant role in ensuring the successful treatment and recovery of these patients. Surgeons and anesthesiologists must be aware of strategies required to deal with this special subgroup.…”
Section: Introductionmentioning
confidence: 99%